Development of real-time flight control system for low-cost vehicle - Du, Yongliang (Cranfield University, 2011)
In recent years, more and more light aircraft enter our daily life, from Agricultural applications, emergency rescue, flight experiment and training to Barriers to entry, light aircraft always have their own advantages. Thus, they have become more and more popular. However, in the process of GDP research about Flight Control System design for the Flying Crane, the author read a lot of literature about Flight Control System design, then noticed that the research in Flight Control System have apparently neglected to Low-cost vehicles. So it is necessary to do some study about Flight Control System for this kind of airplane. The study will more concern the control law design for ultra-light aircraft, the author hopes that with an ‘intelligence’ Flight Control System design, this kind of aircraft could sometimes perform flying tasks according to a prearranged flight path and without a pilot. As the Piper J-3 cub is very popular and the airframe data can be obtained more easily, it was selected as an objective aircraft for the control law design. Finally, a ¼ scale Piper J-3 cub model is selected and the aerodynamics coefficients are calculated by DATCOM and AVL. Based on the forces and moments acting on the aircraft, the trim equilibrium was calculated for getting proper dynamics coefficients for the selected flight conditions. With the aircraft aerodynamics coefficients, the aircraft dynamics characteristics and flying qualities are also analyzed. The model studied in this thesis cannot answer level one flying qualities in the longitudinal axis, which is required by MIL-F- 8785C. The stability augment system is designed to improve the flying qualities of the longitudinal axis. The work for autopilot design in this thesis includes five parts. First, the whole flight profile is designed to automatically control aircraft from takeoff to landing. Second, takeoff performance and guidance law is studied. Then, landing performance and trajectory is also investigated. After that, the control law design is decoupled into longitudinal axis and later-directional axis. Finally, simulation is executed to check the performance for the auto-controller.
Keywords: Classical control; modern control; Root locus; ultra-light aircraft; autopilot; takeoff; landing; Pole placement; PID; flight simulation